Education Development Goals (EDGs) and socio-economic democratic consolidation: reflections on regimes mandates, objectives, agendas, and targets in Yobe State, Nigeria - Abbas, Ali Ibrahim; Ku Samsu, Ku Hasnita; Ab. Halim, Adlina; Saidu, Mohammed Bashir (Macrothink Institute, 2018)
Education development is now considered an important element in combatting poverty, exploitation and promoting democracy. Hence, it not surprising that at global and local levels there have been rapid but in some cases, the gradual transformation of education development system spearheaded by governments and development bodies through policy formulation and implementation. In Nigeria, this development is however diverse as each sub-national levels depicts a different scenario in the country. Since the creation of Yobe state in 1991 during the military regime up to 1999 when democracy was restored across the country, the state has been tagged as an “Educationally Disadvantaged State” (EDS). Yobe had, therefore, continued to battle with efforts to reforms its educational system both in theory and practice. This paper describes and analyses the pursuit of Education Development Goals (EDG) from 2009-2015 by Governor Gaidam’s regime in Yobe state, Nigeria as a tool for socio-economic democratic consolidation in the state. The narrative is based on perceptions and experiences of education stakeholders in the state. This qualitative study involved 28 interviews interview with key informants and the review of various policy documents, which intend to underscore the real essence for and modality of pursuing the EDGs by this regime. The study delineates the state government’s mandates, strategic objectives, agenda and target setting towards achieving overall education development under this democratic regime. Emphasis has been laid on the process, content and context of the regime’s key development agenda which may either positively or negatively affect the state’s nature of socio-economic democratic consolidation.